Documentation of sediment core PS128_42-1 - Klages, Johann Philipp; Müller, Juliane; Lembke-Jene, Lester; Tiedemann, Ralf (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, 2024)
Reliable knowledge about the maximum extent of the grounding line during the Last Glacial Maximum (LGM) some 20,000 years ago and its subsequent inland retreat is particularly sparse for the Mac.Robertson continental shelf. Here, we present sedimentological and sediment-physical data as well as core photographs and X-radiographs for sediment core PS128_42-1 from the mid-Nielsen Basin – a cross-shelf palaeo-ice stream trough – that are used to contribute to a reliable spatiotemporal framework of past grounding line dynamics since the LGM and to establish detailed facies analyses for describing past environmental change across the shelf.